Pengaruh Likuiditas, Tingkat Utang, Dan Efisiensi Modal Kerja Terhadap Kemampuan Operasional Pada Badan Layanan Umum Daerah (Blud) Puskesmas Kota Palembang 2018-2022 - danendra, sheren azzahra danendra; Nelly Masnila; Darul Amri (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2024)
ABSTRACT THE INFLUENCE OF LIQUIDITY, DEBT LEVELS, AND WORKING CAPITAL EFFICIENCY ON THE OPERATIONAL CAPABILITY OF THE PALEMBANG CITY PUSKESMAS Sheren Azzahra, 2024 E-mail : The aim of this research is to determine the effect of liquidity, debt levels and working capital efficiency on operational capabilities at the Palembang City Community Health Center BLUD. This type of research is quantitative. The research population was 42 Community Health Centers in the Palembang City Government Community Health Center BLUD using a purposive sampling technique. The research was carried out from March 2024 to July 2024. Secondary data was collected through financial reports, namely balance sheets and budget realization reports. 7 financial report data were obtained from 42 community health centers that were available. processed using multiple linear regression analysis with the SPSS program. These results indicate that liquidity, debt levels, and working capital efficiency have an impact on operational capabilities at the Palembang City Community Health Center Keywords: liquidity, debt level, working capital efficiency, operational capability v